Discourse connectors: an overview of the history, definition and classification of the term - Kalajahi, Seyed Ali Rezvani; Abdullah, Ain Nadzimah; Mukundan, Jayakaran; Tannacito, Dan J. (IDOSI Publications, 2012)
Many studies have investigated discourse connectors. However, researchers are still grappling with the term in terms of its definition and classification in particular. Many researchers use the term discourse markers (DMs) while others have used terms like linking words, connectives, discourse operators and discourse connectors to refer to the same idea. This paper attempts to better define the term and propose a classification of DCs in written discourse. As is evident from the literature, researchers are unable to agree on the best definition for the term connectors or what is generally known as discourse markers. Researchers in the field have put forward a few different definitions and descriptions of what connectors are and their function in language and some researchers have also developed their own taxonomy and classification for connectors. After reviewing research conducted on connectors, we decided for purposes of this paper to use the term ‘discourse connectors’ mainly because we believe these connectors function to link one portion of information to another one in a text and that while the term discourse marker is a suitable term for spoken discourse, its definition and classification may vary for written discourse. We define DCs as words and expressions that can be accommodated within the text to join one sentence with another sentence or one paragraph to another paragraph or even one idea to another. Finally, we attempt to offer a comprehensive definition and classification of discourse connectors with the aim to provide a better understanding of what DCs are and how they function, with variation from previous reviews of the term.